Applying spatio-chemical analysis to grassland ecosystems for the illustration of chemoscapes and creation of healthscapes - Pereira, Fabiellen Cristina; Gregorini, Pablo (Frontiers in Sustainable Food Systems, 2022)
Grasslands are heterogeneous landscapes composed by a diversity of herbaceous and shrub vegetation that varies not only taxonomically, but biochemically in term of primary and secondary compounds. Plant Secondary Compounds (PSC) have specific nutritional, medicinal and prophylactic properties, to which benefits depend upon dosage, type, arrangements, and concentration that changes between and within plants across time and space. The knowledge of plants’ content of PSC and their distribution in grazing environments would therefore contribute to the design and creation of ruminant’s healthier foodscapes; in other words, healthscapes. Geographic information systems (GIS) have been used extensively for landscape visualization and assessment, through several spatial analysis techniques applied for the creation of virtual maps to add valuable information to a particular environment. Given the acknowledge of plants and their composition, GIS emerges as a readably available and low-cost tool to assess and evaluate the distribution of plants with beneficial PSC in large and heterogeneous foodscapes. We present and propose for the very first time, the application and use of GIS to determine spatial distribution of PSC rich plants with nutraceutical properties to illustrate, visualize, and generate healthscapes for grazing ruminants. We present healthscapes maps created using botanical composition analyses and advanced image classification methods to illustrate the distribution of plants regarding its PSC and nutraceutical properties. Such maps add an extra dimension and perspective of plants chemical composition, enabling graziers to visualize in space and time centres of nutrition and prophylactics or medicines, contributing to advanced grazing management decisions towards more productive, sustainable, and healthy grazing systems. The valuable information behind the mapped PSC advances the understanding of the nutritional ecology of grazing environments and foodscapes, introducing a new dimension to holistic of pastoral livestock production systems.